Do regional party primaries affect the ideological cohesion of political parties in multilevel systems? Evidence from Spain. (November 2020) - Debus, Marc; Navarrete, Rosa M
Parties have strong incentives to present a relatively cohesive policy position to the voters across different levels of a political system. However, the adoption of inclusive forms of candidate selection methods like primaries could result in the selection of top candidates for elections on the subnational sphere who are not favoured by the party leadership. This is often seen as a threat to high levels of intra-party programmatic cohesion. Because subnational party organizations depend to a significant degree on the support from their national party, we argue that regional party branches that selected their top candidates by means of a primary adopt a policy position that deviates less strongly from the one of their national party. However, candidates selected by primaries might need to be responsive to the preferences of their regional selectorate, so that the incentives for parties at a regional level to deviate substantially from the position of their national party organization could increase. By analysing the content of 150 regional election manifestos of Spanish parties, we find that if a party's top candidate for a regional election is selected in a primary, then the policy distance between the respective regional and national party decreases. However, this effect is not observable for recently founded parties.